2016
DOI: 10.1128/jvi.00053-16
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus and Chromatin: Role of the CHD1 Chromatin Remodeler in the Virus Life Cycle

Abstract: Influenza A virus requires ongoing cellular transcription to carry out the cap-snatching process. Chromatin remodelers modify chromatin structure to produce an active or inactive conformation, which enables or prevents the recruitment of transcriptional complexes to specific genes; viral transcription thus depends on chromatin dynamics. Influenza virus polymerase associates with chromatin components of the infected cell, such as RNA polymerase II (RNAP II) or the CHD6 chromatin remodeler. Here we show that ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 77 publications
2
24
0
Order By: Relevance
“…The recombinant minireplicon assay was performed essentially as described [47]. In brief, cultures of HEK293T cells (2.5 × 10 6 cells) were transfected with a mixture of plasmids expressing the RNP components (pCMVPA, 2.5 ng; pCMVPB1, 12.5 ng; pCMVPB2, 12.5 ng; and pCMVNP, 500 ng) and a genomic plasmid expressing a viral RNA (vRNA)-like chloramphenicol acetyltransferase reporter gene (pHHCAT, 500 ng) using the calcium phosphate technique [48].…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant minireplicon assay was performed essentially as described [47]. In brief, cultures of HEK293T cells (2.5 × 10 6 cells) were transfected with a mixture of plasmids expressing the RNP components (pCMVPA, 2.5 ng; pCMVPB1, 12.5 ng; pCMVPB2, 12.5 ng; and pCMVNP, 500 ng) and a genomic plasmid expressing a viral RNA (vRNA)-like chloramphenicol acetyltransferase reporter gene (pHHCAT, 500 ng) using the calcium phosphate technique [48].…”
Section: Methodsmentioning
confidence: 99%
“…Despite extensive characterization of CHD family proteins, their role in shaping host-pathogen interactions has not been much investigated. Yet, there are few reports supporting the involvement of CHD1 in the case of influenza A virus, and both CHD1 and CHD2 in the case of HIV as positive regulators2627. Furthermore, RNAi screen carried out in D. melanogaster S2 cells identified the involvement of CHD7/Kismet in antimicrobial humoral response50.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that CHD1 and CHD2 proteins play a pivotal role in the replication of influenza and HIV viruses2627. Both viruses replicate inside the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations